Pelatihan Aplikasi Mendeley sebagai Instrumen Citation dan Reference Manager Artikel Ilmiah bagi Akademisi di Kota Madiun - Pratiwi, Damar Isti; Prasetya, Henry Widya; Atmaja, Dadang Sanjaya (Jurnal Pengabdian UNDIKMA, 2022)
The community service about training in using Mendeley application as a citation and reference manager instrument in writing article for university students in Madiun aims to share knowledge for academicians in writing article citation and reference manager using Mendeley. The participants of this community service are the university students in Madiun. This activity was done through discussion and simulation in Zoom meeting. It was started with planning and socialization for a month through social media. The simulation was done through Zoom meeting in a day. Evaluation of this activity was done by giving questionnaire for all participants at the end of the training. The results of the evaluation showed that the training of article citation and reference manager in writing article benefits for the university students in writing appropriate APA 7th edition-citation.